Hmong transnational identity: the gendering of contested discourses - Roberta Julian (Hmong Studies Journal, 2004)
Hmong women throughout the diaspora are increasingly expressing ‘what it means to be Hmong’ and ‘what it means to be a Hmong woman’ in a variety of media that constitute western popular culture. At the same time, Hmong women residing in different nation-states live Hmong femininity differently. This paper explores the contested nature of Hmong identity through an exploration of discourses and practices at global and local levels, with a particular emphasis on their gendered dimensions. The paper argues that global narratives of Hmong identity are analytically distinct from, but empirically intertwined with, the constructions of Hmong identities across transnational social spaces. Through a focus on Hmong in Australia and the United States, the paper highlights the significance of place, generation, gender, religion, class and status as axes of contestation and debate in the construction of Hmong identities.